Предмет: Алгебра,
автор: ayanajenishbekova2
810) Упростите выражение: а) 5 (4х²-2x+1)-2 (10х²– 6х-1); 6) 7 (2y²-5y-3)-4 (3y²-9y-5); в) а (3b— 1) -b (a-3)-2 (ab-a+b); г) х² (4-у²)+y²(x²-7)— 4х (х-3).помогите
Ответы
Автор ответа:
1
Ответ:
Объяснение:
.......
Приложения:
Автор ответа:
1
5(4x²-2x+1)-2(10x²-6x-1)=20x²-10x+5-20x²+12x-2=2x+5
7(2y²-5y-3)-4(3y²-9y-5)=14x²-35y-28-12y²+36y+20=2y²+y-8
a(3b-1)-b(a-3)-2(ab-a+b)=3ab-a-ab-3b-2ab+2a-2b=3a-b
x²(4-y²)+y²(x²-7)-4x(x-3)=4x²-x²y²+x²y²-7y²-4x²+12x²=
12x²-7y²
Похожие вопросы
Предмет: Английский язык,
автор: bakumenkosan
Предмет: Английский язык,
автор: Lyasya7
Предмет: Русский язык,
автор: zemfira1234567
Предмет: Английский язык,
автор: daxa1111